2013
DOI: 10.4028/www.scientific.net/amr.781-784.2609
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Molecular Weight on the Structure and Properties of PAN Precursor

Abstract: The effect of molecular weight on the structure and properties of PAN precursor was studied by the combination of scanning electron microscopy (SEM), X-ray diffraction (XRD) and differential scanning calorimetry (DSC), etc. With the molecular weight increasing, the grooves on the surface become deeper and rougher, the interlayer spacing and crystallite size increase, and the exothermic reaction occurred later. The strength and breaking extension of PAN precursors increase gradually with the molecular weight in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…Thus, the VHMW precursor requires a higher temperature for the oxidative reaction to initiate [13]. Similar results were found by Lin, et al [14].…”
Section: Thermal Oxidationsupporting
confidence: 85%
“…Thus, the VHMW precursor requires a higher temperature for the oxidative reaction to initiate [13]. Similar results were found by Lin, et al [14].…”
Section: Thermal Oxidationsupporting
confidence: 85%
“…Despite the off-circular morphologies of the high-molecularweight PAN fibers, the tensile strength of the precursor and carbon fibers increased with higher molecular weight owing to the increased crystal size and orientation. This was confirmed multiple times by other researchers [33,34]. Although the high-molecular-weight polymer has excellent mechanical properties, the high molecular weight generally induces increased viscosity and subsequent off-circular cross-section.…”
Section: Pan Structure and Molecular Weightsupporting
confidence: 72%
“…Meanwhile, the dispersity ( Ð M ), M w / M n , typically ranges from 1.5 to 3.0 . Molecular weight and molecular weight distribution have been shown to influence the microstructure of resulting carbon fiber . Specifically, Lin et al and Tsai et al have shown that higher molecular weight leads to grooved surfaces and changes in the cross‐section of the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular weight and molecular weight distribution have been shown to influence the microstructure of resulting carbon fiber . Specifically, Lin et al and Tsai et al have shown that higher molecular weight leads to grooved surfaces and changes in the cross‐section of the fiber. Moreover, the high molecular weight fractions in uncontrolled free radical polymerizations tend to be insoluble and cause problems such as gelation during fiber spinning and filtration .…”
Section: Introductionmentioning
confidence: 99%